2021
DOI: 10.3390/foods10040871
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sodium Selenite, Selenium Yeast, and Bacterial Enriched Protein on Chicken Egg Yolk Color, Antioxidant Profiles, and Oxidative Stability

Abstract: The chicken egg is one of nature’s flawlessly preserved biological products, recognized as an excellent source of nutrients for humans. Selenium (Se) is an essential micro-element that plays a key role in biological processes. Organic selenium can be produced biologically by the microbial reduction of inorganic Se (sodium selenite). Therefore, the possibility of integrating Se enriched bacteria as a supplement in poultry feed can provide an interesting source of organic Se, thereby offering health-related adva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 101 publications
0
5
0
Order By: Relevance
“…Many studies have shown that supplementing the diet of laying hens with Se improves their antioxidant capacity (glutathione peroxidase, superoxide dismutase, and catalase) (Han et To produce organic Se, different strains of microorganisms can be used in the microbial reduction pathway. Stenotrophomonas maltophilia (ADS18) has been linked to organic Se-containing proteins that can be used as Se sources in poultry (Dalia et Muhammad et al, 2021). Although Se may help the antioxidant system, there is little scienti c evidence on the effect of this new organic Se source on layers.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that supplementing the diet of laying hens with Se improves their antioxidant capacity (glutathione peroxidase, superoxide dismutase, and catalase) (Han et To produce organic Se, different strains of microorganisms can be used in the microbial reduction pathway. Stenotrophomonas maltophilia (ADS18) has been linked to organic Se-containing proteins that can be used as Se sources in poultry (Dalia et Muhammad et al, 2021). Although Se may help the antioxidant system, there is little scienti c evidence on the effect of this new organic Se source on layers.…”
Section: Introductionmentioning
confidence: 99%
“…Lipid peroxidation reduces the quality and nutritive value of eggs and destroys vitamins, essential amino acids, and other nutrients in egg yolk, resulting in undesirable changes during storage and consumption (34). MDA is one of the end products in the process of lipid peroxidation; therefore, the MDA content may reflect the degree of lipid peroxidation in egg yolk (35). Our study found both quercetin and daidzein significantly decreased MDA content and improved the oxidation stability in egg yolk layers.…”
Section: E Ects Of Quercetin and Daidzein On Mda And Lipid Content In...mentioning
confidence: 58%
“…Egg quality includes the index of yolk color, albumen height, Haugh unit, breaking force and so on. Usually, the higher the yolk color measurement of an egg, the more popular it is with consumers, and yolk color is influenced by pigment content in feed, hen breed and antioxidant contents [23]. In this study, cysteamine supplementation elevated the egg yolk color in CAU-3 hens at the peak stage of egg production.…”
Section: Discussionmentioning
confidence: 70%